New development: Marketization versus politicization in a perpetual strive for public audit independence. Issue 3 (3rd April 2023) - Thomasson, Anna
IMPACT: This article contributes to the debate about audit independence by providing insight into the different phases of the audit process and how and why audit activities are subject to influence from different interests. This insight can be used by regulators who are interested in developing policies to improve audit quality.